Joining or Exiting the Defined Benefit Division Superannuation Scheme of UniSuper - John Christie (Australasian Accounting, Business and Finance Journal, 2023)
The Defined Benefit Division of UniSuper is a large defined benefit superannuation scheme in Australia for public universities. Unlike public service superannuation schemes in Australia, it is not guaranteed by the employers. This has previously led to a reduction in benefits of the scheme due to expected funding shortfalls. This paper examines longstanding and more recent issues with the funding of the Defined Benefit Division. Recent changes to superannuation laws in Australia may result in further benefit reductions for the scheme in the future. Should new eligible employees join the Defined Benefit Division? What form of retirement benefit should be taken by retiring Defined Benefit Division members? The paper examines these two key questions. Employees who are contemplating joining the Defined Benefit Division, or those Defined Benefit Division members about to retire, have some very important decisions to make.
Keywords: Superannuation; Universities; Defined benefit; Indexed pension; Retirement